2019
DOI: 10.1371/journal.pone.0220993
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of Pacific white shrimp (Litopenaeus vannamei, Boone 1931) in response to acute hepatopancreatic necrosis disease caused by Vibrio parahaemolyticus

Abstract: Acute hepatopancreatic necrosis disease (AHPND), caused by marine bacteria Vibrio Parahaemolyticus , is a huge problem in shrimp farms. The V . parahaemolyticus infecting material is contained in a plasmid which encodes for the lethal toxins PirAB Vp , whose primary target tissue is the hepatopancreas, causing sloughing of epithelial cells, necrosis, and massive hemocyte infiltration. To get a better understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 88 publications
2
16
0
Order By: Relevance
“…in shrimp intestines is higher than its metabolic activity. This is in agreement with previous studies, where innate immune system activation of shrimp, such as Marsopenaeus japonicus and L. vannamei , was evaluated in response to V. alginolyticus and V. parahaemolyticus infections, demonstrating that they could modulate host signalling proteins and activate their defence system in the presence of potentially pathogenic microorganisms, activating genes that have activities related to immune response mechanisms, such as prophenoloxidase and superoxide dismutase activities, and apoptosis in the hepatopancreas tissue 36 , 37 as well as in the intestinal epithelium 38 . Therefore, a selective biological pressure exerted by the host on the metabolic activity of this bacteria could be occurring, while stimulating the shrimp's immune system by functioning as a natural probiotic necessary for the life cycle of the host.…”
Section: Discussionsupporting
confidence: 92%
“…in shrimp intestines is higher than its metabolic activity. This is in agreement with previous studies, where innate immune system activation of shrimp, such as Marsopenaeus japonicus and L. vannamei , was evaluated in response to V. alginolyticus and V. parahaemolyticus infections, demonstrating that they could modulate host signalling proteins and activate their defence system in the presence of potentially pathogenic microorganisms, activating genes that have activities related to immune response mechanisms, such as prophenoloxidase and superoxide dismutase activities, and apoptosis in the hepatopancreas tissue 36 , 37 as well as in the intestinal epithelium 38 . Therefore, a selective biological pressure exerted by the host on the metabolic activity of this bacteria could be occurring, while stimulating the shrimp's immune system by functioning as a natural probiotic necessary for the life cycle of the host.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, it has been reported that the PirA VP -and PirB VP binary toxin encoded by V. parahaemolyticus can be neutralized by either hemocyanin or anti-lipopolysaccharide factor (16). In addition, the interaction between immune and metabolism appears to play a role in AHPND response in hepatopancrease in shrimp (17,18). Until now, due to the lack of AHPND-tolerant lines of shrimp, no effort could be made to examine the gene expression profiles of AHPND-susceptible and tolerant lines of shrimp.…”
Section: Introductionmentioning
confidence: 99%
“…These mostly include studies on host–viral mechanisms in shrimps for the identification of immune gene repertoire (Xue et al., 2013; Zeng et al., 2013). Some studies pertaining to host antibacterial mechanisms have also been recorded that understands the molecular pathways responsible for shrimp defence in response to infectious diseases (Qin et al., 2018; Velazquez‐Lizarraga et al., 2019; Zeng et al., 2020). From the Illumina sequencing data sets obtained in the present study, we found a total of 1,911 differentially expressed genes in between the Mr_VH and Mr_C transcriptome libraries, out of which a significant proportion of the contig sequences (1,805) were downregulated.…”
Section: Discussionmentioning
confidence: 99%